2002
DOI: 10.1108/09684880210446866
|View full text |Cite
|
Sign up to set email alerts
|

Assuring quality service in higher education: registration and advising attitudes in a private university in Lebanon

Abstract: The first encounter of students at universities is the administrative office, which leaves a lasting imprint for their entire experience in higher education. With the exponential growth of higher education in the Middle East, private universities face hardened competition in the overall retention of students. Registrar and academic advising offices are vital components to the university as well as the front end to the universities' service quality. This study attempts to measure student attitudes of registrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 2 publications
3
33
2
4
Order By: Relevance
“…Consequently institutions of higher education are competing for the most promising students, their customers, by applying scientific business principles to recruit and retain these students (De Jager 2006). Abouchedid and Nasser (2002) argued that the service quality concept in higher education is inextricably linked to the competitive service and success of an institution. Service quality serves to meet the basic objective of enrolment and retention of students at the HE institutions (Maringe and Gibbs 2009).…”
Section: Service Quality and Its Measurement In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently institutions of higher education are competing for the most promising students, their customers, by applying scientific business principles to recruit and retain these students (De Jager 2006). Abouchedid and Nasser (2002) argued that the service quality concept in higher education is inextricably linked to the competitive service and success of an institution. Service quality serves to meet the basic objective of enrolment and retention of students at the HE institutions (Maringe and Gibbs 2009).…”
Section: Service Quality and Its Measurement In Higher Educationmentioning
confidence: 99%
“…While some of the studies on service quality in higher education were conceptual with global coverage others had specific country interests including: Australia (Chua 2004;Wright and O'Neil 2002); UK (Hill 1995;Pareda et al 2007;Telford and Masson 2005); Portugal (Oliveira-Brochado and Marques 2007); Singapore (Tan and Kek 2004); China and Hong Kong (Kwan and Ng 1999); Lebanon (Abouchedid and Nasser (2002); and South Africa (Cloete and Bunting 2000;De Jager 2006).…”
Section: Introductionmentioning
confidence: 98%
“…En consonancia con los resultados obtenidos, es posible establecer que las universidades privadas también se preocupan de asegurar la calidad de sus instituciones, tal como ocurre en las universidades privadas del Medio Oriente, donde la calidad de servicio que le entregan a sus estudiantes es un aspecto crucial de resguardar, razón por la cual las oficinas de registro académicos son consideradas como elementos vitales para otorgar un buen servicio a los estudiantes [2].…”
Section: Resultsunclassified
“…Shaw et al (1995) reported that "although the concern for assessment currently sweeping the West is not so pronounced in the Gulf". Some universities in the Middle East assess particular portions of their operations, such as registration and advising (Abouchedid and Nasser, 2002), university training of occupational attainment (Nasser and Abouchedid, 2005), and e-learning challenges in the Arab World (Abouchedid and Eid, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%